2016
DOI: 10.1002/chem.201602621
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Mixed‐Valent Eu2+/Eu3+ in Strontium Formate Frameworks for Multichannel Photoluminescence

Abstract: Cooperative performance of mixed-valent Eu(2+) /Eu(3+) in single-compound phosphors offers significant advantages in color rendering and luminescence efficiency, but their synthesis is challenging because of Eu(2+) oxidation. Using the tunable nature of the metal-ion nodes in metal-organic frameworks (MOFs), we present an in situ reduction and crystallization route for preparing MOFs and doping Eu(2+) /Eu(3+) with a controlled ratio. These materials exhibit rich photoluminescence, including intrinsic- and sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Recent examples on Tb 3+ /Eu 3+ ‐doped systems not discussed in these reviews and deserving remark are the works of Liu et al and Li et al The first paper reported an in situ reduction and crystallization route for preparing Eu 2+ /Eu 3+ ‐doped MOFs. The materials exhibit intrinsic‐ and sensitized‐emissions of Eu 2+ and Eu 3+ ions, besides a long‐lived luminescence from ligand‐to‐metal charge transfer.…”
Section: Luminescent Thermometers Based On Ln3+ Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent examples on Tb 3+ /Eu 3+ ‐doped systems not discussed in these reviews and deserving remark are the works of Liu et al and Li et al The first paper reported an in situ reduction and crystallization route for preparing Eu 2+ /Eu 3+ ‐doped MOFs. The materials exhibit intrinsic‐ and sensitized‐emissions of Eu 2+ and Eu 3+ ions, besides a long‐lived luminescence from ligand‐to‐metal charge transfer.…”
Section: Luminescent Thermometers Based On Ln3+ Ionsmentioning
confidence: 99%
“…The materials exhibit intrinsic‐ and sensitized‐emissions of Eu 2+ and Eu 3+ ions, besides a long‐lived luminescence from ligand‐to‐metal charge transfer. A ratiometric luminescent thermometer was demonstrated based on the linear relation between temperature and the intensity ratio of Eu 3+ (at 618 nm) and Eu 2+ (at 427 nm) emissions between 9 and 293 K . The second example described a MOF‐based thermometer based on Eu 3+ ‐to‐ligand back energy transfer and operative over a wide temperature range, including the physiological (12–320 K), upon excitation with visible light (450 nm) …”
Section: Luminescent Thermometers Based On Ln3+ Ionsmentioning
confidence: 99%
“…In particular, the 5 D 0 state is a single level without any Stark splitting in any hosts. This can avoid the convolution of overlapping luminescence lines from different energy levels …”
Section: Introductionmentioning
confidence: 99%
“…Recently,w eh ave investigatedt he preparation, luminescence characteristics, and thermal stability of an ew phosphor of Gd 8 4 ] 3À with at etrahedral symmetry (T d ), aknown luminescence center,has the efficiento pticala bsorption of the charge transfer (CT) in the near-UVregion. [6] The self-activated emission is ab road peak at l = 400-750 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation